Tract(atus) 23: La teoría es espera - Grelet, Gilles; Agirregoikoa, Juan Pérez (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Gilles Grelet Title (Spanish): Tract(atus) 23: La teoría es espera Translated by (French to Spanish): Juan Pérez Agirregoikoa Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 110 Page Count: 1 Citation (Spanish): Gilles Grelet, “Tract(atus) 23: La teoría es espera,” traducido del francés por Juan Pérez Agirregoikoa, Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 110.